AB0827 High Prevalence of Hallux Valgus in Gouty Patients Requiring Urate Lowering Therapy. (15th July 2016) - Blandin, C.; Forien, M.; Dieudé, P.; Ottaviani, S.
Abstract : Background: Hallux valgus (HV) is a common pathology leading to pain and deformation of the first metatarsophalangeal joint (MTP1). Gout preferentially affects MTP1 joint and gives disability and pain. It was suggested that gouty patients could have more severe hallux valgus. Objectives: We aimed to determine: 1) the prevalence of HV in gouty patient starting urate lowering therapy (ULT) and 2) the potential factors associated with HV. Methods: In this transversal single center study, we included patient with proven gout (presence of monosodic urate crystal in synovial fluid) requiring ULT. All patients underwent ultrasonography of MTP1s and radiography of the feet. Demographic and clinical characteristics were collected for each patient. Serum uric-acid (SUA) level was assessed at baseline. One trained ultrasonographer, blinded to radiographic measure, assessed at the MTP1 joints, US-evidenced urate deposits (double contour [DC] sign and/or tophi) before starting ULT. HV was analyzed, blinded to clinical and US data, according to the radiographic measure of hallux abductus (HA) angle, and the intermetatarsal (IM) angle. HV was defined by HA angle ≥20° and/or IM angle ≥10°. Correlation between US findings and different HV angles was estimated by the Spearman coefficient of correlation. Results: A total of 43 patients (93% of male patients) with untreated proven gouty patients were studied. The median age was 63.0 [IQR 57.0–73.0] years old. Median disease duration was 3.0 [1.0–6.0] years. Clinical tophi were found in 24% of patients. The median MDRD creatinin clearance and serum uric acid level were 63.0 [IQR 39.8–78.0] ml/mn/1.73m 2 and 507 [IQR 446–601] μmol/l, respectively. Ultrasound assessment of MTP1 joints revealed a DC sign and tophus in 59.3% and 69.8% of joints, respectively. The median size of US tophi were 11.7 [IQR 9.4–13.7] mm. Radiography found HV in 61.9% of feets (72% of patients). The median IM and HA angles were 8.9 [IQR 7.0–10.0] mm and 20.5 [IQR 15.1–26.0] mm, respectively. The percentage of MTP1 joints with US tophus or DC sign was not significantly higher in patients with HV. No correlation was found between the size of US tophus and HA angle ( P =0.54). However, IM angle tended to be correlated with the size of US tophus ( P =0.08). We did not observe any correlation between age, gender, SUA levels, presence of clinical tophus, creatinine clearance, disease duration, number of attacks and presence of HV. Conclusions: Our results suggest a high prevalence of HV in gouty patients requiring ULT. Despite a tendency to have an association between US tophus size and IM angle, we did not observed any correlation between size of tophus and presence of HV. Our patients having a long disease duration, we might hypothesize that a sooner treatment could prevent the apparition of HV in these patients. Disclosure of Interest: None declared